ANALISIS USAHATANI CABAL MERAH (CAPSICUM ANNUM L) DI SUBAK ISEH, DESA SINDUWATI, KECAMATAN SIDEMEN, KABUPATEN KARANGASEM, BALI - Goya Suwastawa, I Nyoman (dwijenAGRO, 2010)
The research was carried out to study farmer' s income and profit gained from an ordinary chili farm. The research was conducted at Subak lseh of Sinduwati village, Sidemen sub district, Karangasem regency. Thirty six farmers who cultivate ordinary chili with monoculture system ware taken randomly as samples. The research result show that the average large farm business was                         0.1353 ha   with          5,555.85 kg products/ha. While the approximate revenue was Rp 38,884,577.48/ha with the chili price of Rp 7,000.00/kg. Meanwhile farmer's expenditure was Rp I 2,825,949.69/ha, so farmer's income and net profit were Rp 38,884,577.84 and Rp 26,058,627.78/ha, where Return-Cost Ratio was 3.03. it means that the chili farm business give much benefit to the farmers. Key word : Farm business, Revenue, Pro fil, Return-Cost-Ratio